Ultraviolet radiation excited strong red-emitting LaAlO3:Eu3+ nanophosphors: Synthesis and luminescent properties. Issue 5 (1st April 2017) - Lee, Soo Hyun; Du, Peng; Bharat, L. Krishna; Yu, Jae Su
Abstract: We synthesized the trivalent europium ions (Eu 3+ ) doped lanthanum aluminate (LaAlO3, LAO) nanophosphors by a solvothermal method. Their structural, morphological, and luminescent properties were systematically investigated. The obtained nanoparticles possessed single nanocrystallinity with a rhombohedral structure. For the excitation originating from the charge transfer band (O 2- to Eu 3+ ions) under 320 nm illumination, the featured emissions of Eu 3+ ions were detected in all the compounds. The optimum doping concentration of Eu 3+ ions in LAO was about 9 mol% and the concentration quenching was dominated by dipole-dipole interaction. Furthermore, the Judd-Ofelt (J-O) theory was used to estimate the J-O intensity parameters. Based on the temperature-dependent PL emission spectra, the thermal stability was analyzed and the activation energy was obtained to be 0.234 eV. Meanwhile, the decay time, color coordinate/purity, and cathodoluminescence behaviors of the synthesized nanophosphors were also studied. These characteristics make the Eu 3+ -doped LAO nanoparticles a promising red-emitting phosphor for both ultraviolet-based white light-emitting diodes and field-emission displays.